(untitled) (Research, Society and Development, 2020)
The Unified Health System - SUS came to prioritize the service to all population free of charge and is composed of divided systems for better care in basic, medium and high complexity care. Basic care is represented by the basic health unit - UBS that aims to promote prevention and health promotion. With the purpose of supporting and amplifying these health care offers, the Family Health Support Centers (NASF) were set up as multiprofessional teams that work in an integrated manner with the Family Health teams (ESF). And the speech pathologist is one of the NASF team members. In addition, the NASF aims to strengthen health care guidelines in which they understand integrative and complementary practices. To objective identify the speech-language pathology contribution in the assistance of users of the Integrative and Complementary Practices Centers. This is a cross-sectional field research with a quantitative approach, composed of 28 professionals, who are part of the three CPICS of this municipality, which are the Nucleus of Integrative and Complementary Practices (NuPICS) - Five Elements, CPICS Harmonia, CPICS Equilibrium of Being. With opinion number 1,876,467 obtained by approval of the research in the Ethics Committee, the questionnaire-instrument and analysis were used according to the provision in Excel 2010. The results implied the presence of complaints In the CPICS. This fact shows the absence of the speech-language pathologist in integrative and complementary practices in the services of the municipality of João Pessoa, which would directly contribute to the expansion of integrative and complementary care to SUS users, considering the wide range of resources and actuation possibilities of this Care.